Block hybrid method for delay differential equations in variable step size - Wong, Chui Ching (2021)
Delay differential equations have often been used in engineering and science studies. This project proposed the new block-hybrid method to resolve the retarded delay differential equations in variable step size. This technique is constructed on a couple of explicit and implicit equations applied in predictorcorrector mode. The Lagrange interpolation polynomial had been implemented together to come close to the delay solutions. The step size is variated according to the local truncation error. The proposed technique had been analyzed by comparing the numerical results with the existing method when solving the retarded delay differential equations.